2022
DOI: 10.1016/j.dld.2021.08.017
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy evaluation of sodium-glucose co-transporter 2 inhibitors for patients with non-alcoholic fatty liver disease: An updated meta-analysis

Abstract: Background: In recent years, sodium-glucose co-transporter 2 inhibitors (SGLT2is) have been increasingly used in the treatment of patients with non-alcoholic fatty liver disease (NAFLD). This updated metaanalysis aimed to evaluate the efficacy and safety of SGLT2is for patients with NAFLD. Methods: PubMed, Embase, Cochrane Library, Web of Science, Wan Fang, China National Knowledge Infrastructure and VIP databases were searched for relevant studies from inception to April 30, 2021. Values of weighted mean diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…The primary line of care is weight reduction by adopting a healthy lifestyle (i.e., changes in diet and exercise). Unfortunately, weight loss by lifestyle changes alone is often a challenge for obese patients [ 8 ]. According to a study, fewer than half of patients can reduce their weight with lifestyle interventions alone [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary line of care is weight reduction by adopting a healthy lifestyle (i.e., changes in diet and exercise). Unfortunately, weight loss by lifestyle changes alone is often a challenge for obese patients [ 8 ]. According to a study, fewer than half of patients can reduce their weight with lifestyle interventions alone [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…SGLT2i could decrease hepatic fat content and liver enzymes and improve body composition in contrast to other antihyperglycemic drugs, independent of insulin resistance, plasma glucose, and weight loss (19,47). However, other investigations found that improvement in NAFLD is closely associated with body weight and plasma glucose (48,49). Hence, it is yet known whether the positive effects of SGLT2i on hepatic fibrosis and steatosis are attributed to a direct effect of SGLT2i or adjustments of metabolic disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the overall improvement in hepatic steatosis is also found in patients treated with other classes of anti-diabetic drugs, like thiazolidinediones and dipeptidyl peptidase-4 (DPP-4) inhibitors, raising the question of steatosis improvement due to glycemic control [ 148 , 160 , 162 , 170 ]. Moreover, the vast majority of the aforementioned studies are limited by the small sample size, heterogenous inclusion criteria, especially regarding the presence of NAFLD, as well as the duration of follow up, thus meta-analyses have been conducted to better assess the true benefit of SGLT-2i in patients with DM and NAFLD [ 171 , 172 , 173 ]. In the largest one, comprising 9 randomized trials, with 7281 and 4088 patients in the SGLT-2i and control arm, (standard of care (SOC) or placebo), respectively, the use of SGLT-2i resulted in improvement of serum transaminases, body weight, and liver fat as measured by proton density fat fraction.…”
Section: Sglt-2 Inhibitors In Nafldmentioning
confidence: 99%